2018
DOI: 10.1097/mlr.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of ICU Delirium and Coma in the Intensive Care Unit Patient

Abstract: Delirium is associated with substantial costs after accounting for time-varying illness severity and could be 20% higher (∼$22,500) if not for its association with early ICU mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 46 publications
5
83
0
5
Order By: Relevance
“…Complete or partial disorientation at the time of admission of the elderly person was also associated with a higher expenditure on hospitalizations. This finding corroborates the results obtained by Vasilevskis et al 32 , which identified, from a prospective cohort study, that disorientation is directly associated with the increase in expenses related to ICU admissions. The importance of the variable for the phenomenon studied is also confirmed by some of the main instruments used to assess the prognosis of an intensive care stay, such as the Acute Physiology and Chronic Health Evaluation (APACHE II), the Sequential Organ Failure Assessment (SOFA) and the Logistic Organ Dysfunction System (LODS), which use the variable as a criterion in their scores 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Complete or partial disorientation at the time of admission of the elderly person was also associated with a higher expenditure on hospitalizations. This finding corroborates the results obtained by Vasilevskis et al 32 , which identified, from a prospective cohort study, that disorientation is directly associated with the increase in expenses related to ICU admissions. The importance of the variable for the phenomenon studied is also confirmed by some of the main instruments used to assess the prognosis of an intensive care stay, such as the Acute Physiology and Chronic Health Evaluation (APACHE II), the Sequential Organ Failure Assessment (SOFA) and the Logistic Organ Dysfunction System (LODS), which use the variable as a criterion in their scores 33 .…”
Section: Discussionsupporting
confidence: 93%
“…The main finding of this study was that the use of hydromorphone was associated with more days alive and DFCF while on ECMO support, with more time free of coma and with ~75% less narcotic exposure when compared with fentanyl. These findings are relevant to patient‐centered outcomes because the development of delirium in critically ill patients is associated with higher mortality, increased time on mechanical ventilation, increased length of stay, and higher costs 17‐24 …”
Section: Discussionmentioning
confidence: 99%
“…Historically, delirium rates among mechanically ventilated ICU populations were consistently 70-75%, and the duration of delirium has consistently proven an independent predictor of longer lengths of stay, higher mortality, greater cost of care, and alarming rates of acquired dementia that lasts years following illness [70][71][72][73]. Given these facts, it is important to carry into the pandemic the knowledge that delirium in mechanically ventilated patients can be reduced dramatically to 50% using a culture of lighter sedation and mobilization via the implementation of the safety bundle called the ABC-DEFs promoted by the Society of Critical Care Medicine (SCCM) in their ICU Liberation Collaborative [37,38].…”
Section: Covid-19: Icu Delirium Management-potential Problems and Solmentioning
confidence: 99%